7x-2x2=0

Simple and best practice solution for 7x-2x2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-2x2=0 equation:



7x-2x^2=0
a = -2; b = 7; c = 0;
Δ = b2-4ac
Δ = 72-4·(-2)·0
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(7)-7}{2*-2}=\frac{-14}{-4} =3+1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(7)+7}{2*-2}=\frac{0}{-4} =0 $

See similar equations:

| 5^(2x-3)=6 | | 2/3x108-3/4=9/12x108 | | 5^2x-3=6 | | 2.5x=1.1x+1200 | | F(x)=x2+4x+7 | | 3.5-0.04x=0.82 | | 3y+1/5=2y+7/3 | | x-17=(5/9)x | | 1/3x+5/6=x-1/2 | | 12x-4+42=17x+6 | | X*(x+5)=204 | | 7(b+3)=10b+9-3(b-4) | | -54=-6x+7(6x+18) | | -8y-10=2y+20 | | (2x-4)=(6x-6) | | 43p^2+156p-48=0 | | -3/4=5x | | -33=4x-3(x+15) | | 12+b4=24 | | -11=b-16 | | -14=k-3 | | 6x+2(-4x+15)=42 | | -3(2x-4=24 | | √a+1=√a−6+1a+1=a-6+1 | | 113=-5x-3(x-11) | | 40d=60(12-d) | | x(x+1)=x+23 | | 5-(1+m)=6(m-4) | | -147=7x+3(-6x-5) | | 24=4+10x | | 1/2(8x+10)=1/3(15x+15) | | 2|x+2|+8=10 |

Equations solver categories